Commonalities and Discrepancies in the Relationships between Behavioural Outcome and the Results of Neuroimaging in Brain-Damaged Patients - Hans J. Markowitsch; Pasquale Calabrese (Behavioural Neurology)
Variables which are of influence in establishing clear predictions of neuropsychological alterations from neuroradiological data (and vice versa) are documented and discussed. It is concluded that personality factors and the kind and locus of brain lesions are the most crucial determinants. The locus of the brain damage may have cumulative effects either when it is situated in a strategic place (usually within the white matter, affecting interneuronal communication) or when various types of lesions appear superimposed (combination of focal and diffuse lesions). Consequently, the consideration of the patient's personality background and of as many neuropsychological facts as possible may considerably increase the validity of outcome predictions. When static or dynamic neuroimaging fails to show abnormalities in spite of obvious psychological alterations, an intensive neuropsychological documentation may even replace neuroradiology.